Prospective study on anti-ganglioside antibodies in childhood Guillain–Barré syndrome. Issue 1 (18th August 2006) - Schessl, J; Koga, M; Funakoshi, K; Kirschner, J; Muellges, W; Weishaupt, A; Gold, R; Korinthenberg, R
Abstract : Background: Antiganglioside antibodies have been reported to play a part in the pathophysiology of Guillain–Barré syndrome (GBS). Aims: To investigate the prevalence and correlation of anti-ganglioside antibodies with clinical data in children with GBS in a multicentre clinical trial. Methods: Immunoglobin (Ig)G and IgM to GM1, GM1b, GD1a, GalNAc–GD1a, GD1b, GT1a, and GQ1b were measured by ELISA in sera obtained before treatment. In addition, serological testing for Campylobacter jejuni was carried out. In parallel, a group of adults with GBS and a control group of children without GBS or other inflammatory diseases were evaluated. Results: Sera from 63 children with GBS, 36 adults with GBS and 41 children without GBS were evaluated. Four of the children with GBS showed positive IgG to GM1, in one case combined with anti-GalNAc–GD1a and in one with anti-GD1b. Two others showed isolated positive IgG to GD1b and GT1a. One showed increased anti-GalNAc–GD1a IgM. In 5 of the 63 children, serological evidence of a recent infection with C jejuni was found, and this correlated significantly with the raised antibodies (p = 0.001). In the control group without GBS, no child showed positive IgG, but one showed anti-GalNAc–GD1a IgM. Compared with the adults with GBS, the frequency of antibodies in children was insignificantly lower. In our study, patients with positive antibodies did not show a more severe GBS course or worse outcome than those who were seronegative, and we could not show an increased incidence of axonal dysfunction. Conclusions: In some children with GBS, one can detect raised IgG against various gangliosides, similar to that in adults. A recent infection with C jejuni is markedly associated with the presence of these antibodies. However, in contrast with what has been reported in adults, in this study we were unable to show a negative effect of these findings on the clinical course.